Sustainability-Oriented STEM-PjBL: Improving Students’ Science Process Skills through Experimental Activities - Wardatul Husna; Roza Zulfira; Mentari Darma Putri; Yuni Syahraini; Afrahun Naziah (Jurnal Pendidikan Fisika, 2026)
Science process skills (SPS) are essential competencies in physics education because they enable students to investigate scientific phenomena, apply concepts, and communicate evidence-based findings in real-world contexts. However, students often have difficulty formulating hypotheses, planning experiments, and systematically presenting observational results, indicating the need for instructional approaches that explicitly support scientific inquiry. This study aimed to examine the effect of sustainability-oriented STEM Project-Based Learning (STEM-PjBL) physics worksheets on high school students’ SPS in renewable energy topics. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed at SMAN 2 Banda Aceh during the 2023/2024 academic year. The sample consisted of 70 tenth-grade students selected through simple random sampling at the class level and divided into an experimental class (n = 35) and a control class (n = 35). The experimental class used sustainability-oriented STEM-PjBL worksheets that integrated the stages of the Engineering Design Process, while the control class used conventional PjBL worksheets. Data were collected using a 20-item SPS test and observation sheets, and then analyzed using normality and homogeneity tests, normalized gain scores, and an independent-samples t-test. The results showed that the experimental class achieved a higher N-gain score of 0.70 in the high category, compared with 0.63 in the medium category for the control class. The posttest difference was statistically significant (p = 0.030), and the experimental class showed higher gains across all SPS indicators, particularly in predicting and communicating. The novelty of this study lies in explicitly integrating sustainability principles into the Engineering Design Process and mapping them to integrated SPS indicators. These findings suggest that sustainability-oriented STEM-PjBL worksheets provide an evidence-based instructional model for strengthening scientific inquiry and contextual learning in physics education on renewable energy.